The Problematic Arabic Linguistics - Bassal, Mohammad; Omran, Zeina (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research deals with the issue of the Arabic Linguistics, tries to characterize its problems and determines it causes; in order to reach scientific results that help them to provide solutions. It presents beginning of the nature of the science of term and its scientific term and determines what is distinct from the vocabulary of other language. Then turn to go into the problems of the term Arabic language, describe its realty and presents its problems that destabilizes its conventional characteristics, try to determine the causes of these problems and suggests to over com them. It presents the efforts of Arab linguistics institutions to solve these problems and identifies their weakness. It discusses the problematic usage of the traditional Arabic linguistics against the modern linguistics concepts, presents the different views on this problem and proposes its vision as a just ification and ends with recommendations for solving the problems of the Arabic linguistics